A comparative study on the grid integrated wind energy conversion systems (WECS) using different generator models. (1st January 2012) - Gidwani, Lata; Tiwari, H.P.
A huge number of wind generators are going to be connected with the existing network in the near future. Therefore, it is necessary to analyse various models of wind energy conversion systems (WECS) for the purpose of studying the impacts upon grid. This paper presents comparative study on grid connected WECS having two different wind turbine generator systems (WTGS): model 1 [WTGS having doubly fed induction generators (DFIGs)] and model 2 [WECS having permanent magnet synchronous generators (PMSG)]. Both models are connected to AC grid through an efficient power electronic interface. Transient simulations are carried out under the condition of sudden short circuit disturbance and effect of increased generator inertia constant, friction factor and base speed is analysed. The power quality is also analysed in terms of total harmonic distortion (THD) for both models and steps are taken to improve the power quality by reducing THD.